EVALUASI PENERAPAN CARA PRODUKSI PANGAN YANG BAIK UNTUK INDUSTRI RUMAH TANGGA (CPPB-IRT) PADA PRODUKSI SUSU PASTEURISASI DI UMKM X, MAGETAN - Denna Rianda Toni; Muhammad Mar'ie Sirajuddin (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Pasteurized milk can be a medium for the growth of microorganisms or other contamination, if the handling processing, and storage processes are not good. Therefore, it is necessary to evaluate Good Food Production Methods for Home Industries (CPPB-IRT) on pasteurized milk production in UMKM X in order to determine the quality assurance system and food safety for the food processing industry that has been set by government regulations. The purpose of this practical work is to find out the application of CPPB IRT in UMKM X in the production of pasteurized milk. The data were obtained by interview, observation, documentation, literature study, and check sheet methods. Then the data obtained were categorized according to their suitability and an analysis of the non-conformance aspects was carried out using a Pareto diagram. Based on the analysis that has been carried out, it is known that in the pasteurized milk production process in UMKM X are deviations from the application of CPPB-IRT aspects in 11 aspects of 14 aspects. Of the 11 aspects, there are 53 discrepancies. Based on the results of the analysis using Pareto diagrams, it is known that the cause of the problem of CPPB-IRT incompatibility in UMKM X in the production of pasteurized milk comes from the aspects of buildings and facilities; hygiene facilities and activities; and process control. X in pasteurized milk production is at IRTP level IV (four)